2018
DOI: 10.4047/jap.2018.10.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of implant component fractures in external and internal type: A 12-year retrospective study

Abstract: PURPOSEThe aim of this study was to compare the fracture of implant component behavior of external and internal type of implants to suggest directions for successful implant treatment.MATERIALS AND METHODSData were collected from the clinical records of all patients who received WARANTEC implants at Seoul National University Dental Hospital from February 2002 to January 2014 for 12 years. Total number of implants was 1,289 and an average of 3.2 implants was installed per patient. Information about abutment con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
1
12
2
Order By: Relevance
“…This study only assessed patients receiving Ankylos implants because most of the implants used during the study period were of this brand. This eliminated any fracture rate differences possibly attributable to differences in implant morphology and abutment-implant connection methods [6]. The Ankylos implant body is made of pure titanium grade 2, easier to process than grade 4 and reported to show higher shear contact strength when in contact with bone [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study only assessed patients receiving Ankylos implants because most of the implants used during the study period were of this brand. This eliminated any fracture rate differences possibly attributable to differences in implant morphology and abutment-implant connection methods [6]. The Ankylos implant body is made of pure titanium grade 2, easier to process than grade 4 and reported to show higher shear contact strength when in contact with bone [24].…”
Section: Discussionmentioning
confidence: 99%
“…Fracture of the veneering material; loosening or fracture of the abutment screw; and fracture of the framework, abutment, or implant are the worst-case scenarios and have been reported following long-term prosthesis use [4,5]. The fracture rate of implant components, including the implant, abutments, and abutment screws, is 5.6% [6]. Bruxism and the crown-implant ratio (C/I) are possible causes of internal stress that lead to mechanical complications [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Removing the screw remnant from the implant after a fracture is both challenging and time consuming 353637. A 12-year retrospective study showed that screw fractures occurred most frequently among components in external connection implants, and the fractured screws were not retrieved in 6.2% of cases 38. From the clinical point of view, when screw fracture occurs, it is important to remove the fractured remnant.…”
Section: Discussionmentioning
confidence: 99%
“…The number of cases was insufficient to obtain statistically significant results, and few existing studies have supported this finding. However, the reason why screw fracture occurs more frequently in the external connection type and abutment fracture or fixture fracture more frequently in the internal connection type was explained by Yi et al [26] in 2018. When a force is applied to an implant, the internal connection type and the external connection type show structurally different force distributions.…”
Section: Discussionmentioning
confidence: 99%